Problematic presentation and use of efficacy measures in current trials of CGRP monoclonal antibodies for episodic migraine prevention: A mini-review. (January 2020) - Tfelt-Hansen, Peer; Diener, Hans-Christoph; Steiner, Timothy J
Background: In trials of monoclonal antibodies against calcitonin gene-related peptide or its receptor for prevention of episodic migraine, we observed two problematic aspects: a) The graphic presentations; b) the methods of calculating "response rates" (≥50% decrease of monthly migraine days from baseline). Observations: Decrease in monthly migraine days is presented, over time, in figures on a downward (negative) scale from zero at baseline, with the ordinate stopped just beyond the maximum effect of the active drugs. In one trial, decreases in monthly migraine days were −1.8 after placebo, −3.2 after erenumab 70 mg and −3.7 after erenumab 140 mg, with the ordinate stopped at −4.5. The reader can perceive only a relative 2-fold benefit of erenumab versus placebo. If, however, treatment periods are compared with baseline in bar charts, MMDs persisting after treatment in the same trial can be illustrated as follows, creating a different perception: 78% for placebo, 61% for erenumab 70 mg, and 55% for erenumab 140 mg. In the nine trials, "response rates" defined as above were calculated in five different ways, taking different numbers of treatment months into account in comparisons with the one-month baseline. This makes comparisons impossible. Suggestions for improvements: Mean monthly migraine days before and after treatment should be presented in a bar chart. Such figures, presenting persisting MMDs, are more clinically relevant and less misleading than decreases from baseline. The definition and methods of calculating and presenting "50% response rates" should be standardized by the Drug Trial Committee of the International Headache Society.